2005
DOI: 10.1007/s11010-005-7322-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of oxidative stress in cyclophosphamide-challenged hepatic tissue by DL-α-lipoic acid

Abstract: The present study investigated the protective effect of DL-alpha-lipoic acid on the tissue peroxidative damage and abnormal antioxidant levels in cyclophosphamide (CP) induced hepatotoxicity. Male Wistar rats of 140 +/- 20 g were categorized into four groups. Two groups were administered CP (15 mg/kg body weight once a week for 10 weeks by oral gavage) to induce hepatotoxicity; one of these groups received lipoic acid treatment (35 mg/kg body weight intraperitoneally once a week for 10 weeks; 24 h prior to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 29 publications
8
29
0
Order By: Relevance
“…Cellular mechanisms of toxicity are mediated by an increase in the free radicals through intracellular phosphoramide mustard and acrolein, the principle alkylating metabolites of CP (Tripathi & Jena, 2008). In the present study, CP administration damaged the liver, and this observation is consistent with the previous reports (Elkiran et al, 2007;Selvakumar et al, 2005). CP administration under different conditions and doses has been demonstrated to be an excellent model to produce the syndromes of both oxidative stress and hepatic damage (Mathew & Kuttan, 1997;Stankiewicz et al, 2002;Sulkowska et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Cellular mechanisms of toxicity are mediated by an increase in the free radicals through intracellular phosphoramide mustard and acrolein, the principle alkylating metabolites of CP (Tripathi & Jena, 2008). In the present study, CP administration damaged the liver, and this observation is consistent with the previous reports (Elkiran et al, 2007;Selvakumar et al, 2005). CP administration under different conditions and doses has been demonstrated to be an excellent model to produce the syndromes of both oxidative stress and hepatic damage (Mathew & Kuttan, 1997;Stankiewicz et al, 2002;Sulkowska et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Cellular antioxidant defenses involving the enzymes, SOD, CAT, and GPx play an important role against ROS generation during oxidative stress and protect tissues including lung from oxidative damage [57][58][59][60]. SOD catalyzes dismutation of the superoxide anion to H 2 O 2 and O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that therapeutic doses of CP could be toxic to liver (Snover et al 1989;Sulkowska et al 2002). CP is metabolized via the hepatic P450 enzymatic system resulting in the formation of 4-hydroxycyclophosphamide and its tautomer aldocyclophosphamide which induce an oxidative stress by producing hydroxyl radicals and altering the antioxidant status of a cell (Selvakumar et al 2005). Other findings suggest that CP depresses antioxidant defense in liver while its metabolism generates superoxide anions and hydrogen peroxide (H 2 O 2 ) (Singh et al 2014).…”
mentioning
confidence: 99%